THE RELATIONSHIP OF THE USE OF 3 MONTHS DMPA INJECTING CONTRACEPTION WITH MATERNAL WEIGHT INCREASE AT BAUMATA PUBLIC HEALTH CENTER - Nur, Siti Nur Asyah Jamillah Ahmad; Henukh, Dina M.S; Pay, Frida S (Jurnal Kesehatan Al-Irsyad, 2021)
Background: The World Health Organization (WHO) reports data on injection contraceptive users worldwide about 45%. BKKBN data in 2017 shows that the use of contraception in Indonesia is 63.6% consisting of injectable family planning (29.0%), pills (12.2%/), implants (4.7%), IUDs (4.7%). ) and others. Data shows that couples of childbearing age (EFA) in the province of East Nusa Tenggara (NTT) 0.8% choose to use condoms, 56.6% injections, 11.5% pills, 7.2% IUDs, 0.4% MOP, 5.1% MOW, 18.3% implants. Based on the pattern of choosing contraceptives in the city of Kupang 2.2% chose to use condoms, 50.7% injections, 13.0% pills, 10.9% IUDs, 0.0% MOP, 5.6% MOW, and those who chose implants. 17.7%. Based on data in 2020 at the Baumata Health Center, the number of active family planning participants was 2,192 participants, of which 80.15% used injectable contraceptives, 16.83% used pills, 0.86% used steady contraception, 2.1% used implants, and 0.04 using a condom. The purpose of this study was to analyze the relationship between the use of DMPA 3-month injectable contraceptives with maternal weight gain at the Baumata Health Center. Methods: The design used in this study was a cross sectional research design. Where the dependent variable is weight gain, the independent variable is DMPA 3-month injectable contraception. The population in this study were all mothers of DMPA injection family planning acceptors at the Baumata Health Center. The sample was selected by purposive sampling technique. Then the data were analyzed by bivariate analysis to test the presence or absence of the influence of the independent variable on the dependent variable. The researcher used the chii square test. Results: Chi-Square test analysis at = 0.05, it can be seen that the value of P = 0.001 <0.05, which means Ha is accepted if the probability (Asymp Sig <0.05). Conclusion: There is a relationship between the use of DMPA 3-month injectable contraceptives with maternal weight gain at the Baumata Health Center Keywords: DMPA Injectable Contraception, Weight Gain